Inhibitory properties of crude microalgal extracts on the in vitro replication of cyprinid herpesvirus 3 - Stefanie Fritzsche (Nature Portfolio, 2021)
Abstract Microalgae are possible sources of antiviral substances, e.g. against cyprinid herpesvirus 3 (CyHV-3). Although this virus leads to high mortalities in aquacultures, there is no treatment available yet. Hence, ethanolic extracts produced with accelerated solvent extraction from six microalgal species (Arthrospira platensis, Chlamydomonas reinhardtii, Chlorella kessleri, Haematococcus pluvialis, Nostoc punctiforme and Scenedesmus obliquus) were examined in this study. An inhibition of the in vitro replication of CyHV-3 could be confirmed for all six species, with the greatest effect for the C. reinhardtii and H. pluvialis crude extracts. At still non-cytotoxic concentrations, viral DNA replication was reduced by over 3 orders of magnitude each compared to the untreated replication controls, while the virus titers were even below the limit of detection (reduction of 4 orders of magnitude). When pre-incubating both cells and virus with C. reinhardtii and H. pluvialis extracts before inoculation, the reduction of viral DNA was even stronger (> 4 orders of magnitude) and no infectious viral particles were detected. Thus, the results of this study indicate that microalgae and cyanobacteria are a promising source of natural bioactive substances against CyHV-3. However, further studies regarding the isolation and identification of the active components of the extracts are needed.